2017
DOI: 10.5194/acp-2016-1161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observational evidence for the formation of ocean DMS-derived aerosols during Arctic phytoplankton blooms

Abstract: <p><strong>Abstract.</strong> The connection between marine biogenic dimethyl sulfide (DMS) and the formation of aerosol particles in the Arctic atmosphere was evaluated by analyzing atmospheric DMS mixing ratios, aerosol particle size distributions and aerosol chemical composition data that were concurrently collected at Ny-Ålesund, Svalbard (78.5° N, 11.8° E) during April and May 2015. Measurements of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…For the measurement of major ions, a 47‐mm (diameter) disk filter was punched out from the filter samples. Major ions, including Na + , on the disk filter were extracted in 50 ml of Milli‐Q water and analyzed by a Dionex ion chromatography system (Thermo Fisher Scientific Inc., Waltham, MA, USA), as described in Park et al ().…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the measurement of major ions, a 47‐mm (diameter) disk filter was punched out from the filter samples. Major ions, including Na + , on the disk filter were extracted in 50 ml of Milli‐Q water and analyzed by a Dionex ion chromatography system (Thermo Fisher Scientific Inc., Waltham, MA, USA), as described in Park et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Secondary aerosol production occurs through the nucleation of gaseous precursors (e.g., sulfuric acid, ammonia, halocarbons, isoprene, and monoterpenes; Kulmala & Kerminen, ; Kirkby et al, ; Ehn et al, ; Ovadnevaite et al, ). Recently, several field and laboratory studies have shown that the physiochemical properties of primary and secondary marine organic aerosols are significantly related to biological activities at the ocean surface (O'Dowd et al, ; Facchini, Decesari, et al, ; Facchini, Rinaldi, et al, ; O'Dowd et al, ; Park et al, ; Rastelli et al, ; Jang, Park, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summer, different processes isolate the Arctic marine boundary layer from southern aerosol sources (both natural and anthropogenic), namely: the northward migration of the atmospheric polar front, the efficient wet scavenging by drizzling stratocumulus clouds, and the formation of surface inversion layers (3,25,26). These processes result in extremely low aerosol concentrations, which favor new particle formation from local gaseous precursors (23,25,27,28). Recent measurements and associated modeling have shown instances where DMS controls the formation of ultrafine particles (23,28), which can grow large enough to act as cloud condensation nuclei (CCN) (23,25).…”
mentioning
confidence: 99%
“…These processes result in extremely low aerosol concentrations, which favor new particle formation from local gaseous precursors (23,25,27,28). Recent measurements and associated modeling have shown instances where DMS controls the formation of ultrafine particles (23,28), which can grow large enough to act as cloud condensation nuclei (CCN) (23,25). Thus, changes in Arctic Ocean EDMS could alter aerosol populations, light scattering, and cloud-seeding activity (26,27,29,…”
mentioning
confidence: 99%